STUDENTS’ PERCEPTIONS OF DIFFICULTIES IN THE LISTENING SECTION OF THE TOEFL AMONG ENGLISH EDUCATION STUDENTS OF FKIP UNIVERSITAS RIAU - Greti Aritonang, Sona; Afrianto Daud; Fadly Azhar (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study investigated students’ perceptions of difficulties in the listening section of the TOEFL among English Education students of FKIP Universitas Riau. The study aimed to identify which listening indicators were perceived as the most difficult by students. A descriptive quantitative method supported by interviews was employed. The participants consisted of 177 English Education students selected using stratified random sampling. Data were collected through a questionnaire adapted from Phillips’ (2001) TOEFL listening indicators and semi-structured interviews to support the quantitative findings. The results revealed that several listening indicators were perceived as highly difficult by the students. Indicators categorized as high difficulty included identifying speakers’ implied meanings, understanding idiomatic expressions, recognizing almost negative expressions, and distinguishing similar sounds. These findings indicate that students experienced significant challenges in comprehending implicit information and specific linguistic features in TOEFL listening tasks. The study suggests that greater instructional emphasis should be placed on these listening indicators to improve students’ listening comprehension skills.